The Effect Of Media Exposure, Environmental Performance, And Meeting Frequency Of Board Of Commissioners On Carbon Emission Disclosure (A Study On Basic Materials Companies Listed On The Indonesia Stock Exchange In 2020-2022) - Fauziah, Aminatul Tanaya; Andayani, Wuryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Carbon emission disclosure is one of the corporate responsibilities in participating in efforts to address global climate change. As such, this study aims to test and provide empirical evidence on how media exposure, environmental performance, and frequency of board of commissioners’ meetings affect the carbon emission disclosure. This study applies a quantitative approach, analyzing the data using multiple linear regression. The samples include 17 basic materials companies listed on the Indonesian Stock Exchange between 2020 and 2022, selected purposively, yielding a total of 51 observable data points. Data processing and analysis are to be conducted using SPSS 25. The study's results indicate that media exposure and environmental performance positively affect carbon emission disclosure. Whilst this study does not prove the effect of the board of commissioners' meeting frequency on carbon emission disclosure.